Upaya Perlindungan Hukum Terhadap Penyalahgunaan Bantuan Sosial: Aplikasi Kawal.Id Sebagai Platform Kelompok Marginal Terdampak Covid-19 di Indonesia - Annisa Nur Rahma Ramadhani; Nur Fadliansyah Abubakar; Rahmah Maulidah (Jurnal Legislatif, 2021)
Abstract Since Indonesia was hit by the Covid-19 Pandemic, the government has tried to optimize the economic life of the community, especially marginal groups by simultaneously providing social assistance. The reality of the increasing misuse of social assistance to marginal groups occurs due to the lack of application of the principles of accountability and transparency from the government reflecting legal injustice. This is in line with recipients of social assistance who are not well-targeted, corruption, until the social assistance is not given to the community regarding the right to equal life insurance. This paper describes the solution to the problem as an effort to protect the law through the Kawal.Id application with a case approach. The analysis shows that the Kawal.Id application is oriented towards optimizing data validation of marginalized groups in an efficient manner. In the implementation process, harmonization and collaboration between students and the Indonesian National Police is a key mechanism. So that the goal that is concentrated by the use of application ideas can be an answer to the gloomy existence of social assistance abuse that robs marginalized groups of rights during the Covid-19 pandemic. Keywords: Abuse of Social Assistance; Kawal.Id; Marginal Group. Abstrak Sejak Indonesia dilanda Pandemi Covid-19 pemerintah berupaya mengoptimalkan kehidupan ekonomi masyarakat khususnya kelompok marginal dengan melakukan pemberian Bantuan Sosial (bansos) secara simultan. Realita meningkatnya penyalahgunaan bansos terhadap kelompok marginal terjadi akibat minimnya penerapan asas akuntabilitas dan transparansial dari pemerintah mencerminkan ketidakadilan hukum. Hal ini selaras dengan penerima bansos yang tidak tepat sasaran, korupsi, hingga tidak diberikannya bansos tersebut kepada masyarakat telah merampas hak penjaminan hidup yang setara. Tulisan ini mendeskripsikan solusi permasalahan sebagai upaya perlindungan hukum melalui aplikasi Kawal.Id dengan pendekatan kasus. Analisis menunjukkan, aplikasi Kawal.Id berorientasi pada pengoptimalisasian validasi data masyarakat kelompok marginal secara efisien. Dalam proses pelaksanaannya, harmonisasi dan kolaborasi antara mahasiswa dan Kepolisian RI adalah suatu mekanisme utama. Sehingga tujuan yang terkonsentrasi oleh pemanfaatan gagasan aplikasi dapat menjadi jawaban atas suramnya eksistensi penyalahgunaan bansos yang merampas hak kelompok marginal di masa pandemi Covid-19. Kata Kunci: Kawal.Id; Kelompok Marginal; Penyalahgunaan Bansos.